“It [Diabetes] is From God and I Need to Take Care of Myself”: Type 1 Diabetes Self-Management Among Adolescents and Their Parents in Jordan - Momani, Aaliyah M.; Callery, Peter; Lin, Yin-Ling; Abduelkader, Raghad Hussein; AL Akash, Hekmat Y. (Current Diabetes Reviews, 2022)
Background: Type 1 diabetes is the most common endocrine condition among adolescents. Diabetes self-management can be challenging during adolescence. Objective: The objective of this study is to understand how adolescents and their parents manage type 1 diabetes in Jordan. Methods: Constructivist grounded theory methodology principles were used to achieve the study aim. A total of 48 participants were recruited using purposive and theoretical sampling techniques, including adolescents and their parents. Data were collected (October 2016 - April 2017) using 38 semi-structured, audio-recorded interviews (one-to-one or joint interviews based on participants’ preferences). Data were collected and analyzed concurrently using different levels of coding, constant comparative analysis, and memo writing. This study was approved by relevant ethics committees from the University of Manchester and Jordan University Hospital. Results: The theme of living with diabetes is presented and discussed in this article. Culture emerged as the central theme; two aspects of culture are presented in this article: collectivism and cultural beliefs. Conclusion: This study identified that diabetes self-management could be influenced by the culture in which Jordanian adolescents live in as well as being shaped by their religious beliefs. These findings are potentially transferable to other Arab and non-Arab countries that share similar cultural aspects and religious beliefs.
Keywords: culture